2023
DOI: 10.1002/jum.16213
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Monitoring During Microwave Hyperthermia Based on BP‐Nakagami Distribution

Abstract: ObjectiveThe purpose of this study is to accurately monitor temperature during microwave hyperthermia. We propose a temperature estimation model BP‐Nakagami based on neural network for Nakagami distribution.MethodsIn this work, we designed the microwave hyperthermia experiment of fresh ex vivo pork tissue and phantom, collected ultrasonic backscatter data at different temperatures, modeled these data using Nakagami distribution, and calculated Nakagami distribution parameter m. A neural network model was built… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The Nakagami distribution was introduced recently [1]. This distribution has been applied in ultrasound images [2], microwave hyperthermia [3], cataract stiffness [4], and many other applications. The Nakagami distribution is a probability distribution with two parameters that is related to the gamma distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The Nakagami distribution was introduced recently [1]. This distribution has been applied in ultrasound images [2], microwave hyperthermia [3], cataract stiffness [4], and many other applications. The Nakagami distribution is a probability distribution with two parameters that is related to the gamma distribution.…”
Section: Introductionmentioning
confidence: 99%
“…High-intensity focused ultrasound (HIFU), radiofrequency ablation (RFA), and microwave ablation (MWA) are the most frequently used thermal ablation techniques in clinics. [11][12][13] Many studies have demonstrated that MBs can accelerate HIFU-induced temperature increases, enlarge the ablation region, and distort and shift the ablation position. 9,14 However, conflicting results regarding the effects of MBs on RFA have been reported.…”
mentioning
confidence: 99%